2019
DOI: 10.4321/s1575-06202019000300003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictive factors of Chlamydia trachomatis genital infection in inmates 25 to 65 years old in four Catalan prisons

Abstract: Badalona (Barcelona). Centre of epidemiological studies on sexually transmitted infections and AIDS of Catalonia (CEEISCAT). Department of Health. Generalitat of Catalonia. Badalona (Barcelona). Research Institute Germans Trias i Pujol (IGTP). Badalona (Barcelona). CIBER Epidemiology and Public Health (CIBERESP). 3 Centre of epidemiological studies on sexually transmitted infections and AIDS of Catalonia (CEEISCAT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60% 3,15,16,19,24,26,31,34,44 . Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7% 14,16,17,21,24,34,43,44 . One study reported that, more than 58% had of their participants' high education 14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60% 3,15,16,19,24,26,31,34,44 . Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7% 14,16,17,21,24,34,43,44 . One study reported that, more than 58% had of their participants' high education 14 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 15 , 16 , 19 , 24 , 26 , 31 , 34 , 44 Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7%. 14 , 16 , 17 , 21 , 24 , 34 , 43 , 44 One study reported that, more than 58% had of their participants' high education. 14 In one included study, 95.5% of incarcerated people had incomplete primary education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations